Attitude of Stakeholders Towards IARI-Post Office Linkage Extension Model - Sahoo, Alok Kumar; Burman, R. Roy; Lenin, V.; Sajesh, V.K.; Sarkar, Sujit (Indian Journal of Extension Education, 2021)
Agricultural extension eventually evolves to cater a diverse need of a large number of farmers in India. Complementing and supplementing public extension system, IARI-Post Office Linkage Extension Model initiated as an alternate extension approach during 2009 in collaboration with KVKs for transfer of improved critical inputs (crop varieties) to the remote rural farmers. To capture the subjective pattern of preference towards the model and to express their qualitative preference in quantitative way attitude was measured towards the model. Out of the sample beneficiaries, most of the farmers of Sitapur (Mean Score = 4.17) and Buxar (Mean Score = 4.03) expressed favourable attitude towards seeds quality. Majority expressed favourable attitude towards seed sources credibility than other sources, interaction with fellow farmers, willingness to pay the seed and postage cost, and willingness for model continuity. Around one-tenth of farmers had neutral attitude as they were more cosmopolite having more exposure, contact with other extension agencies. Some beneficiaries expressed negative attitude due to less seeds availability, lack of clarity in regular seed supply to the same person by the model. There should be regular sensitization by ICAR-IARI, KVK to the Branch Post Masters and fellow farmers for understanding the concept of model and execution of the same to make it sustainable. Branch Post Masters and KVK scientists’ highly favourable attitude could further expand and replicate the model in different locations by different ICAR organizations.
Keywords: Attitude; IARI-Post Office Linkage; Model; Stakeholders